NHC-Catalyzed reaction of enals with hydroxy chalcones: diastereoselective synthesis of functionalized coumarins - Bhunia, Anup; Patra, Atanu; Puranik, Vedavati G.; Biju, Akkattu T. (Organic Letters, 2013)
The N-heterocyclic carbene-catalyzed annulation of enals with 2'-hydroxy chalcones afford cyclopentane-fused coumarin derivatives with an excellent level of diastereocontrol. The reaction tolerates a broad range of functional groups; 25 examples are given, and a preliminary mechanistic investigation is provided.

Facile synthesis of gamma-ketophosphonates by an intermolecular stetter reaction onto vinylphosphonates - Patra, Atanu; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2014)
The atom-economic and practical N-heterocyclic carbene (NHC) catalyzed Stetter reaction for the synthesis of gamma-ketophosphonates by the reaction of aromatic aldehydes with vinylphosphonates is reported. The NHC derived from N-mesitylimidazolium salt (IMes) was an effective catalyst for this transformation, and the products were formed in moderate to good yields.

N-Heterocyclic carbene-catalyzed enantioselective synthesis of functionalized cyclopentenes via alpha,beta-unsaturated acyl azoliums - Mondal, Santigopal; Yetra, Santhivardhana Reddy; Patra, Atanu; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Highly enantioselective NHC-organocatalyzed synthesis of functionalized cyclopentenes proceeding via alpha,beta-unsaturated acyl azolium intermediates is reported. The organocascade reaction of modified enals with malonic ester derivatives having a gamma-benzoyl group involves the Michael-intramolecular aldol-beta-lactonization-decarboxylation sequence to deliver cyclopentenes in good yields and excellent ee values.

Diastereoselective synthesis of cyclopentanone-fused spirooxindoles by N-heterocyclic carbene-catalyzed homoenolate annulation with isatilidenes - Patra, Atanu; Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Chemistry Frontiers, 2015)
N-Heterocyclic carbene (NHC)-catalyzed formal [3 + 2] annulation of α,β-unsaturated aldehydes with N-substituted isatilidenes resulting in the diastereoselective synthesis of cyclopentanone-fused spirooxindoles is demonstrated. Mechanistically, the reaction proceeds via the generation of homoenolate equivalent intermediates from NHC and enals, which on interception with isatilidenes afford spiroheterocyclic compounds bearing an all-carbon quaternary spiro-center in moderate to good yields and generally with high diastereoselectivity. Moreover, the functionalization of the spirooxindoles as well as the initial studies on the enantioselective version of this reaction are presented.

N-Heterocyclic carbene-catalyzed diastereoselective synthesis of β-lactone-fused cyclopentanes using homoenolate annulation reaction - Mukherjee, Subrata; Mondal, Santigopal; Patra, Atanu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
NHC-catalyzed annulation of enals with 2-enoylpyridines or 2-enoylpyridine N-oxides leading to the diastereoselective synthesis of β-lactone-fused cyclopentanes is reported. The reaction proceeds via the generation of homoenolate equivalent intermediates and tolerates a broad range of functional groups.

Recent advances in the N-heterocyclic carbene (NHC)-organocatalyzed stetter reaction and related chemistry - Yetra, Santhivardhana Reddy; Patra, Atanu; Biju, Akkattu T. (Synthesis‐Stuttgart, 2015)
Recent developments in the N-heterocyclic carbene (NHC)-catalyzed umpolung of aldehydes followed by their interception with activated carbon–carbon double bonds, namely the Stetter reaction, are presented. Advances in the inter- and intramolecular versions of this reaction, enantioselective transformations as well as the use of unactivated olefins in this type of reaction are discussed.

N - heterocyclic - carbene - catalyzed umpolung of imines - Patra, Atanu; Mukherjee, Subrata; Das, Tamal Kanti; Jain, Shailja; Gonnade, Rajesh Ghanshyam; Biju, Akkattu T. (Angewandte Chemie International Edition, 2017)
N-Heterocyclic carbene (NHC) catalysis has been widely used for the umpolung of aldehydes, and recently for the umpolung of Michael acceptors. Described herein is the umpolung of aldimines catalyzed by NHCs, and the reaction likely proceeds via aza-Breslow intermediates. The NHC-catalyzed intramolecular cyclization of aldimines bearing a Michael acceptor resulted in the formation of biologically important 2-(hetero)aryl indole 3-acetic-acid derivatives in moderate to good yields. The carbene generated from the bicyclic triazolium salt was found to be efficient for this transformation.

N-Heterocyclic carbene-catalyzed synthesis of alpha-trifluoromethyl esters - Gelat, Fabien; Patra, Atanu; Pannecoucke, Xavier; Biju, Akkattu T.; Poisson, Thomas; Besset, Tatiana (Organic Letters, 2018)
The N-heterocyclic carbene (NHC)-catalyzed trifluoromethylation of alpha-chloro aldehydes was developed, allowing straightforward access to valuable alpha-trifluoromethyl ester derivatives. The unique combination of an electrophilic trifluoromethylation reagent with NHC catalysis was the key for the functionalization of a broad range of alpha-chloro aldehydes, and the products are formed in moderate to good yields. Investigations of the enantioselective version of this reaction afforded the enantioenriched products in moderate yields with good ee values.

Oxidative NHC catalysis for the generation of imidoyl azoliums: synthesis of benzoxazoles - Patra, Atanu; James, Anjima; Das, Tamal Kanti; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
N-Fleterocyclic carbene (NHC)-catalyzed intramolecular cyclization of aldimines generated from 2-amino phenols and aromatic aldehydes leading to the synthesis of 2-arylbenzoxazoles under mild conditions is presented. The reaction proceeds via the generation of the aza-Breslow intermediates from imines and NHC, which under oxidative conditions form the key imidoyl azoliums and a subsequent intramolecular cyclization furnishes the product. The reaction tolerates a broad range of functional groups, and the products are formed in generally good yields.

Synthesis of 4-difluoromethylquinolines by NHC-catalyzed umpolung of imines - Patra, Atanu (Organic Letters, 2018)
The N-heterocyclic carbene (NHC)-catalyzed umpolung of aldimines for the synthesis of 4-difluoromethylquinoline derivatives is reported. In the presence of NHCs, the intramolecular cyclization of aldimines bearing a moderately electron-poor double bond due to the presence of the −CF3 group likely proceeds via the intermediacy of the aza-Breslow intermediate. The key to the success of this aza-Stetter type transformation is the NHC generated from the bicyclic triazolium salt using DBU as the base.

Synthesis of 2-Aryl naphthoquinones by the cross-dehydrogenative coupling involving an NHC-catalyzed endo-stetter reaction - Ghosh, Arghya; Patra, Atanu; Mukherjee, Subrata; Biju, Akkattu T. (Journal of Organic Chemistry, 2019)
An N-heterocyclic carbene (NHC)-catalyzed intramolecular Stetter reaction proceeding via the endo-fashion was the key step for the transition-metal-free and mild cross-dehydrogenative coupling of 2-cinnamoyl benzal-dehydes allowing for the synthesis of 2-aryl naphthoquinones. In this transformation, the carbene generated from the triazolium salt using Na2CO3 catalyzes the intramolecular Stetter reaction, which was followed by air oxidation to reinstall the C-C double bond.